Seeds, Leaves, and Learning: A Literature Review on the Use of Natural Loose Parts as Educational Play Tools in Early Childhood Education - Fatma Yuhana; Nurlinda (PIJAR: Jurnal Pendidikan dan Pengajaran, 2026)
Early childhood education increasingly recognises natural materials as powerful pedagogical resources. This literature review synthesises evidence on the use of seeds (biji-bijian) and leaves (daun-daunan) as Alat Permainan Edukatif (APE), or Indonesian Educational Play Tools, for supporting holistic learning in children aged three to six. A PRISMA-inspired protocol guided the screening of 287 records retrieved from Scopus, DOAJ, Garuda, Google Scholar, and Crossref between January 2016 and March 2026, yielding 46 sources (28 peer-reviewed articles, 12 books, six policy and report documents) that met inclusion criteria. Findings were synthesised thematically using the loose parts theory of Nicholson (1971) and the affordances perspective on nature-based play. Three patterns emerged: (1) seeds and leaves enrich six developmental domains cognitive, fine motor, language, social-emotional, creative, and eco-spiritual with the strongest evidence in fine motor and pre-numeracy outcomes; (2) the educational power of these materials depends on teacher scaffolding rather than the materials alone; and (3) Indonesian tropical ecology offers an under-utilised reservoir of low-cost APE that aligns with the Kurikulum Merdeka and a culturally Islamic ethos of nature stewardship. The review proposes a taxonomic framework that maps material categories to sensory affordances and pedagogical functions, and identifies methodological gaps regarding measurement validity and longitudinal effects.